2014
DOI: 10.1111/cobi.12374
|View full text |Cite
|
Sign up to set email alerts
|

Identifying correlates of success and failure of native freshwater fish reintroductions

Abstract: Reintroduction of imperiled native freshwater fish is becoming an increasingly important conservation tool amidst persistent anthropogenic pressures and new threats related to climate change. We summarized trends in native fish reintroductions in the current literature, identified predictors of reintroduction outcome, and devised recommendations for managers attempting future native fish reintroductions. We constructed random forest classifications using data from 260 published case studies of native fish rein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
178
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(183 citation statements)
references
References 54 publications
5
178
0
Order By: Relevance
“…; Cochran‐Biederman et al. ). No reproduction was observed in Shinumo Creek, where Humpback Chub translocations were conducted between 2009 and 2014 (Spurgeon et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Cochran‐Biederman et al. ). No reproduction was observed in Shinumo Creek, where Humpback Chub translocations were conducted between 2009 and 2014 (Spurgeon et al.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also have important implications for management and conservation. Stock enhancement, translocations or reintroductions are attractive methods for manipulating density to support endangered populations worldwide (Cochran‐Biederman et al, ; Seddon, Armstrong, & Maloney, ). Here, we demonstrated that different environmental conditions may lead to population‐specific reactions norms to density and by extension to those conservation practices altering density.…”
Section: Discussionmentioning
confidence: 99%
“…Suitable habitat quality and quantity in the recipient stream to meet life history requirements are crucial for the success of reintroduced fish (Cochran‐Biederman et al. ), including Bull Trout (Dunham et al. ; Hayes and Banish ).…”
Section: Discussionmentioning
confidence: 99%